Avaliação de desempenho no setor público: estudo da percepção entre servidores e empregados em um hospital universitário - Palhano, Joemy Lopes (2017)
The use of performance evaluation as an important tool of the strategic people management has been widely recommended by the contemporary theories in the field of Administration. In practice, its implementation is better spread in the private sector, besides being present in the public sector, but in an inceptive way. The performance evaluation is inserted in the performance management context and it can strategically contribute to make an organization reach its goals. In the public sector, there are two important kinds of government employees: "servidores" and "empregados". Due to the specific legislations, these two groups are usually subject to distinct instruments of performance evaluation. Therefore, this paper leads to the question: what are the differences in perception about the performance evaluation those two groups of government employees have? Moreover, the goal is analyzing the differences in perception about the performance evaluation those two groups of government employees have, that, in this context, operate in the same institution. A descriptive and quantitative approach was used as methodology. The data gathering was made in a public hospital in which both kinds of government employees work. The results analysis showed that that are differences and similarities on their perception. The interviewed employees' having a positive perception of the performance evaluation was a fact as well, but there are still some aspects that need to be improved in order to have a better alignment between the performance evaluation, the strategic management and the organizational practices.